Contemporary approaches studying customer experience in tourism research - Jaziri, Dhouha; Rather, Raouf Ahmad (Emerald Publishing, 2022)
"Contemporary Approaches Studying Customer Experience in Tourism Research develops approaches and related methods to understand, analyze, and evaluate the tourist consumption experience under its different forms and stages (before, during and after the experience), offering a broader view by integrating the tourist/customer experience in its development while also considering the role of tourism stakeholders. Embracing the extremities of Customer Experience (CX) and studying its multiple sides through innovative methodological and conceptual frameworks, the volume also provides an in-depth literature review of CX and discusses vital related concepts as the case of consumer value. Contemporary Approaches Studying Customer Experience in Tourism Research also explores the adoption and the implementation of approaches to managing and marketing customer experiences across varied tourism contexts, with an emphasis on revisited interpretive, behavioral, and organizational approaches, highlighting the power of combining qualitative techniques to draw the complexity of the consumption experience. Also laid out are new analytical frameworks related to studying memorable tourist experiences in both digital and offline tourism journeys have attributed a broader consideration of the consumption experience in tourism research."--